2007
DOI: 10.1038/nsmb1212
|View full text |Cite
|
Sign up to set email alerts
|

Structure and nuclear import function of the C-terminal domain of influenza virus polymerase PB2 subunit

Abstract: The trimeric influenza virus polymerase, comprising subunits PA, PB1 and PB2, is responsible for transcription and replication of the segmented viral RNA genome. Using a novel library-based screening technique called expression of soluble proteins by random incremental truncation (ESPRIT), we identified an independently folded C-terminal domain from PB2 and determined its solution structure by NMR. Using green fluorescent protein fusions, we show that both the domain and the full-length PB2 subunit are efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
358
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(379 citation statements)
references
References 32 publications
17
358
1
3
Order By: Relevance
“…Conversely, PB2 mutants with the negatively charged glutamic acid or aspartic acid at position 627 are impaired. Structural analysis has shown that K627 is located on a large solventexposed face of the protein with a predominant positively charged surface (36). Introduction of the E627 mutation disrupted the positively charged surface without altering the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PB2 mutants with the negatively charged glutamic acid or aspartic acid at position 627 are impaired. Structural analysis has shown that K627 is located on a large solventexposed face of the protein with a predominant positively charged surface (36). Introduction of the E627 mutation disrupted the positively charged surface without altering the structure.…”
Section: Discussionmentioning
confidence: 99%
“…2). In addition to the subunit interfaces mentioned above, the atomic structures of domains of the PA and PB2 subunits have been determined 47,55,56,[63][64][65][66][67] but no information on the structure of the polymerase active site in the PB1 subunit is yet available. The data reported allowed the identification of the polymerase cap-binding site in PB2 and established that the endonuclease responsible for cap-snatching resides at the N-terminal region of PA, in agreement with previous genetic contacts detected in the cryo-EM structure of the mini-RNP.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Co-crystal structures of both S. cerevisiae and M. musculus importin-a have been solved in complex with various NLS peptides (52)(53)(54)(55)(56)(57)(58)(59). The three-dimensional structures reveal that NLS peptides bind specifically in two binding grooves created by flexible armadillo (ARM) motifs in the central domain of importin-a (54, 55).…”
Section: Classical Nls Sequencesmentioning
confidence: 99%